Antioxidative study of polysaccharides extracted from red (Kappaphycus alvarezii), green (Kappaphycus striatus) and brown (Padina gymnospora) marine macroalgae/seaweed - Bhuyar, P.; Sundararaju, Sathyavathi; Mohd Hasbi, Ab. Rahim; Unpaprom, Yuwalee; Gaanty Pragas, Maniam; Natanamurugaraj, Govindan (Springer Nature Switzerland, 2021)
Sterile and fresh tissues of three marine macroalgae red, green and brown (Kappaphycus alvarezii, Kappaphycus striatus and Padina gymnospora) collected from Malaysia east costal seas were compared for the antioxidants and polysaccharide composition of sugars as well as the active components. Results obtained showed that polysaccharides isolated from Kappaphycus alvarezii, Kappaphycus striatus and Padina gymnospora) can be used as a source of natural antioxidant compounds as they possess antioxidant potential in which the Padina gymnospora showed 15.56 ± 0.12 mg/mL to be the best antioxidants among all the polysaccharides studied. The hot water extraction method is effective in isolating polysaccharides from studied seaweeds. The GC–MS analysis revealed that there is presence of chemical compounds such as furfural was 25.53% in Kappaphycus alvarezii and 21.04% in Kappaphycus striatus also Padina gymnospora incorporates n- Hexadecanoic acid about 26.31% in seaweed polysaccharides that contribute to their antioxidant activities. Further studies can be done on determining the seaweed species that are available abundantly with the best source of natural antioxidant compounds.